Mapping the Development of Research on Corporate Governance and Corporate Social Responsibility: A Bibliometric Review - Habibi, Fandi Nur Ahmad; Habiburrochman, Habiburrochman (Dinasti Publisher, 2025)
This research elucidates the development and structure of Corporate Governance (CG) and Corporate Social Responsibility (CSR) research through a bibliometric approach. Co-citation, bibliographic coupling, and co-word analyses were employed to unveil patterns of interaction among key concepts. Co-citation analysis revealed three main clusters: CG-CSR Disclosure-Reputation, CG-CSR-Earnings Management, and CG-CSR-Shareholder Value. Bibliographic coupling analysis generated six clusters highlighting interactions between CG and CSR in different contexts. Meanwhile, co-word analysis revealed primary themes in the literature, such as CSR Disclosure, Earnings Management, and Stakeholder Theory. These findings indicate that CG and CSR literature focuses on the interaction between disclosure, earnings management, firm value, and governance mechanisms across various contexts. Future research should enrich the literature by considering previously overlooked theoretical perspectives.